Atrazine treatment with heterogeneous photo-Fenton like oxidation using statically approach - Ebru Çokay (Pamukkale University Journal of Engineering Sciences, 2019)
Atrazine (ATZ) which is a triazine herbicide can be used for the control weeds on agricultural land and it is classified as an endocrine disrupting pesticide. ATZ is persistent in water and soil due to its half-life and slow degradation by means of sunlight and microorganism. The heterogeneous Fenton process is an effective technique for degrading atrazine because of the oxidation and adsorption of pollutants by hydroxyl radical. The hydroxyl radical formation has been accelerated by addition of hydrogen peroxide and magnetite. heterogeneous Photo-Fenton like oxidation were executed to remove atrazine in this study. Effects of independent variables namely the concentrations of atrazine, hydrogen peroxide and magnetite on atrazine removal efficiency were investigated by using the surface response analysis. Atrazine degradation was completely achieved with an hour. Optimal H2O2/Magnetite/ATZ ratio resulting by optimum atrazine removal efficiency (97.5%) was determined as 10/5/0.7, respectively.